Uji Toksisitas Surfaktan Linear Alkilbenzene Sulfonate (LAS) Histologi Insang dan Hati Benih Ikan Kerapu Bebek (Cromileptes altivelis) - Devi Kristianti; Resty Paramitha; Fitri Agustriani; Gusti Diansyah (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2019)
Kristianti et al, 2019.Â Toxicity of Linear Alkilbenzene Sulfonate (LAS) Surfactant Gills and Liver Histology of Humpback Grouper SeedÂ (Cromileptes Altivelis). JLSO 8(1):107-116.LAS is surfactant that is most commonly used because this surfactant is the main cleaning substance contained in detergent. Waste of detergent can give side effects in the tissue of organisms, especially on the gills and liver of fish. The aims of this research were to analyze the toxic effects arised from LAS surfactant to the survival of fish seed experiment with different concentrations, to determine levels of LAS surfactant that are capable to be tolerated and to analyze the gills and liver damage arising from LAS surfactant to fish seed experiment. The test of LAS surfactant toxicity on fish seed experiment was conducted using the laboratory of experimental method, while the testing of gills and liver histology of fish seed experiment with paraffin method and Hematoxylin Eosin (HE) staining. The results showed that LAS surfactant gave toxic effects on Humpback Grouper Seed (Cromileptes altivelis) and gave effect such damage to the gills and liver histology. Toxicity and tissue damage rose as the increase of LAS surfactant concentration. LAS surfactant levels were able to be tolerated by Humpback Grouper Seed test not more than 0,253 mg/l.